The Washington State Constitution - Utter, Robert F. (Robert French), 1930- (Oxford commentaries on the state constitutions of the United States., 2011)
The Washington State Constitution provides an outstanding constitutional and historical account of the state's governing charter. In addition to an overview of Washington's constitutional history, it provides an in-depth, section-by-section analysis of the entire constitution, detailing the many significant changes that have been made since its initial drafting. This treatment, along with a table of cases, index, and bibliography provides an unsurpassed reference guide for students, scholars, and practitioners of Washington's constitution. Previously published by Greenwood, this title has been.